Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Pegawai - Bayu Pamungkas; Idayanti Nursyamsi (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to explore the influence of motivation and work discipline on employee performance in an organization. Motivation as an internal drive plays an important role in influencing morale and individual achievement, while work discipline reflects employee compliance with established rules and standards. Using a qualitative approach and literature review method, this study analyzed various relevant sources to understand the relationship between the two variables and their implications for employee performance. The results show that high motivation and good work discipline significantly contribute to improving employee performance. The combination of these two factors is key in creating a productive and effective work environment. Therefore, organizations need to formulate strategies that are able to increase motivation and work discipline to achieve long-term success.